Verification of Testing Methods for Fully Automated Operation Systems Based on Rail Transit Simulation Testing Platform - MA Didi; YU Saijun; WANG Jingwen (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] In light of the current lack of systematic and scientific evaluation methods for the completeness of subsystem design schemes, and the compatibility/adaptability among subsystems in rail transit FAO (fully automated operation) systems, it is urgently necessary to establish a rail transit simulation testing platform for validation and assessment. [Method] Based on the above testing platform, testing methods are proposed for FAO systems from the perspectives of track and station layouts, signaling and vehicle systems, in order to evaluate whether the design performance of the corresponding systems meets operational requirements. Taking Hefei Rail Transit Line 7 as a case study, the FAO system testing methods are applied to simulate and verify the design performance of the line vehicle system, track alignment and station layout, and signaling system. [Result & Conclusion] During the train simulation test operation, design indicators for tracks and stations such as track minimum curve radius, track gradient, station platform length, line speed limits; signaling system design indicators such as train operating speed, technical speed, travel speed, mainline tracking interval and train dwell time; vehicle system design indicators such as train maximum/average acceleration during startup, train service/emergency braking deceleration are all within acceptable range. The reliability of FAO system testing methods is verified.